Gigantic scaphopods (Mollusca) from the Permian Akasaka Limestone, central Japan. (July 2021) - Asato, Kaito; Kase, Tomoki
Abstract: Paleozoic scaphopods are among the most poorly known mollusks because of their featureless tubular shell morphology and fragmentary preservation. An apical orifice at the posterior end of a conch is a diagnostic character of Scaphopoda that distinguishes them from other groups of animals that produce similar calcareous tubes, but this structure is rarely preserved. A rich molluscan fauna from the Permian Akasaka Limestone in central Japan includes scaphopod shells, and past studies have reported four species, all of which were based on fragmentary specimens. This study recognizes six species in the Akasaka Limestone mainly on the basis of museum/institution collections, and a new genus ( Minodentalium ) and three species ( Prodentalium onoi, M . hayasakai, and M . okumurai ) are described, two known species ( P . akasakensis and P . neornatum ) are redescribed in more detail, and one species ( Prodentalium sp.) is described under open nomenclature. The following eight known species are allocated to the new genus Minodentalium : Plagioglypta furcata Waterhouse, 1980 ; Pl . girtyi Knight, 1940; Pl . subannulata Easton, 1962 ; Dentalium ingens De Koninck, 1843 ; D. meekianum Geinitz, 1866 ; Pl . prosseri Morningstar, 1922 ; Dentalium priscum Münster in Goldfuss, 1842 ; and D . herculeum De Koninck, 1863 . All the species, except for M . hayasakai, are gigantic, reaching 200 mm or more in length. The species richness is the greatest known from a single locality/formation worldwide. UUID: http://zoobank.org/35405b9d-3ba7-40bf-87c5-3f2b550b1a6d